2013
DOI: 10.1186/1471-2164-14-16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the myostatin locus on muscle mass and intramuscular fat content in a cross between mouse lines selected for hypermuscularity

Abstract: BackgroundThis study is aimed at the analysis of genetic and physiological effects of myostatin on economically relevant meat quality traits in a genetic background of high muscularity. For this purpose, we generated G3 populations of reciprocal crosses between the two hypermuscular mouse lines BMMI866, which carries a myostatin mutation and is lean, and BMMI806, which has high intramuscular and body fat content. To assess the relationship between muscle mass, body composition and muscle quality traits, we als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In the present study, the WT and PM strains were grown in various concentrations of Populus hydrolysate (0% or standard medium, 10% and 17.5% v/v Populus hydrolysate) and a genome-wide transcriptomic analysis was conducted at mid-log and late-log time points via RNA-seq. In addition to changes in transcription levels, post-transcriptional regulation of gene expression through the action of sRNA molecules has been demonstrated to play a key role in stress response in Clostridia [ 19 ]; however, the focus of this paper is on changes in gene regulation at the transcriptional level. Two types of comparisons were used to further elucidate the potential mechanism(s) of tolerance for the PM strain: a comparison of the strains in standard and hydrolysate media and a comparison of each strain’s response to Populus hydrolysate-containing media using its gene expression profile in standard medium as a baseline.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the WT and PM strains were grown in various concentrations of Populus hydrolysate (0% or standard medium, 10% and 17.5% v/v Populus hydrolysate) and a genome-wide transcriptomic analysis was conducted at mid-log and late-log time points via RNA-seq. In addition to changes in transcription levels, post-transcriptional regulation of gene expression through the action of sRNA molecules has been demonstrated to play a key role in stress response in Clostridia [ 19 ]; however, the focus of this paper is on changes in gene regulation at the transcriptional level. Two types of comparisons were used to further elucidate the potential mechanism(s) of tolerance for the PM strain: a comparison of the strains in standard and hydrolysate media and a comparison of each strain’s response to Populus hydrolysate-containing media using its gene expression profile in standard medium as a baseline.…”
Section: Introductionmentioning
confidence: 99%
“…With the generation of MSTN-KO animals in recent years, MSTN's molecular function in lipid metabolism has gained increasing attention. It was observed that MSTN inactivation not only reduces overall body fat mass, but to some extent also the intramuscular fat (IMF) content in meat [5][6][7] . As IMF content is an important indicator of meat quality, its reduction would undermine the nutritional and economic value of double muscling animals.…”
mentioning
confidence: 99%
“…), and myostatin locus affects muscle mass and intramuscular fat content in mice (Kärst et al . ). DCN , FMOD and FN1 might be involved in marbling improvement by VA restriction via the control of myostatin action.…”
Section: Discussionmentioning
confidence: 97%